Complete remission of relapsed cervical cancer through immunochemoradiotherapy: Two case reports and three proposed mechanism - Yi-Hao Lin; Hsin-Hong Kuo; Ling-Hong Tseng; Jian-Tai Qiu; Fu-Shun Chang; Cheng-Tao Lin (Wolters Kluwer Medknow Publications, 2016)
Background: In current practice, immunotherapy has been established as an adjuvant rescue therapy for cervical cancer treatment after standard concurrent chemoradiotherapy (CCRT) with tumor recurrence. Carcinoma of the cervix is a relatively chemotherapy-resistant disease. Patients with recurrent cervical cancer have significantly reduced life expectancy, and fewer than 20% of patients survive for 1 year. Therefore, we tried using CCRT after priming and booster immunomodulatory therapy [i.e., immunochemoradiotherapy, (ICRT)]. Case reports: In the first report, a 34 year-old female diagnosed with International Federation of Gynecology and Obstetrics (FIGO) stage IIA cervical cancer with pathological proof of poorly differentiated squamous cell carcinoma was treated with radical surgery. Two years later, she experienced progressive weakness and numbness in her right leg. Computed tomography showed a mass of 8 cm × 7 cm in her right lower pelvis and presacral area with encasement of the right middle ureter. In addition, right hydronephrosis and a metastatic lymph node were suspected in the right iliac vessels. She received standard CCRT with "add on" immunomodulatory agents as a radiosensitizer to augment ICRT. The priming immunomodulatory agents included picibanil [O (i.e., OK-432)], mixed Cervarix (GlaxoSmithKline, London, England) or Gardasil (Merck and Co., Inc., Kenilworth, NJ, USA) viral-like particle vaccine (V) on day 1, and aldesleukin [A (i.e., interleukin-2)] on Day 2. She also started concurrent radiotherapy and palcitaxol (80 mg/m2) on Day 2 and boostered OVA (i.e., picibanil, viral-like particle vaccine, and aldesleukin) again on Day 4 and Day 5. After the ICRT treatment, remarkable improvements occurred by lower sacral pain, regression of the pelvic tumor, and decreased squamous cell carcinoma antigen (SCC-Ag) levels from 33.8 ng/mL to normal. The second case report is a 66-year-old female with FIGO stage IIA cervical adenocarcinoma. She underwent staging surgery, followed by CCRT. She first had a relapse on the supraclavicle node 2 years before receiving CCRT. A left axilla mass was noted 6 years before she started the priming and booster ICRT treatment. Both patients have been disease-free for > 5 years since receiving CCRT. Conclusion: We reported two patients with cervical cancer recurrence after conventional therapy. We combined CCRT and ICRT to augment the host cells' immunosurveillance and reach durable response more than 5 years mimic long-term progression-free survival. These two patients showed promising results.